Estimating Required Number of Nurses in Emergency Department of Imam Ali Hospital Affiliated by Alborz Province Using WISN Method - Ali Ghorbani; Masoomeh Vaziri Seta; Roya Rajaee; Zahra Jamaly; Morteza Najafi; Marziye Najafi (Journal of Evidence Based Health Policy, Management & Economics, 2019)
زمینه و هدف: فراهم بودن نیروی انسانی بخش سلامت از جمله عوامل موثر بر بهبود پوشش خدمات بهداشتی و تحقق بالاترین سطح سلامت جامعه می باشد و Background: The provision of manpower is one of the effective factors on the improvement in the coverage of health services and the realization of the highest community health level and a considerable part of the health budget is devoted to the production and update on human resources. Therefore, the current study aimed to estimate the number of nurses required in the Emergency Department (ED) of Imam Ali hospital based on the proposed method of the World Health Organization, in which the manpower is calculated based on the workload Workload Indicators of Staffing Need (WISN). Methods: This was a cross-sectional descriptive study. The study population was all the nurses working in the emergency department of Imam Ali hospital affiliated by Alborz University of Medical Sciences and their duties in the hospital which was performed using the proposed method of the World Health Organization i.e. WISN in 2018. Determination of their duties and the time and number of times for performing them were carried out during the group discussion session. Results: Based on the research findings, 40 standard nurses were calculated. The studied hospital had 4 nursing staff shortages. The working pressure ratio is 0.91in this study. Conclusion: In the current study, the nursing staff shortage is observed and this shortage caused a high working pressure on the nurses working in the study area. Considering the vital role of nurses in the emergency department, it is recommended to employ and distribute the manpower based on the requirement and workload in the department.